Mannich Reaction: Review of Amine‐Functionalized Lignin Derivatives and Their Applications. Issue 15 (14th April 2023) - Jayaramudu, Tippabattini; Varaprasad, Kokkarachedu; Adamus, Grazyna; Amber Jennings, Jessica; Bumgardner, Joel D.
Abstract: In recent years naturally resourced materials have played a significant role in many applications ranging from biomedical to automotive applications. Among them, lignin has received much attention towards these applications owing to its abundance and readily modified chemical structures. Recent research studies have focused on various chemical modifications of lignin, including the increasingly popular Mannich reaction that aminates the lignin structure to expand the applicability of lignin in advanced fields. This article reviews the recent Mannich reaction‐based lignin developments with different types of amines used in lignin modifications and discusses how the reaction enhances functionality in engineering, biomedical and environmental technology applications. Abstract : Lignin has played a significant role in biomedical to automotive applications. This review summarized the recent Mannich reaction used lignin modifications and their applications i.e, flame retardant, adsorption and other miscellaneous applications. lignin will become a promising renewable aromatic resource for the next generation of applications in the upcoming years.